Enhanced near-Infrared Photoresponse from Nanoscale Ag-Au Alloyed Films - Krayer, Lisa J.; Palm, Kevin J.; Gong, Chen [UNESP]; Torres, Alberto; Villegas, Cesar E. P. [UNESP]; Rocha, Alexandre R.; Leite, Marina S.; Munday, Jeremy N. (American Chemical Society (ACS), 2020)
Alloying of metals provides a vast parameter space for tuning of material, chemical, and mechanical properties, impacting disciplines ranging from photonics and catalysis to aerospace. From an optical point-of-view, pure thin metal films yield enhanced light absorption due to their cavity effects. However, an ideal metal-semiconductor photodetector requires not only high absorption, but also long hot carrier attenuation lengths in order to efficiently collect excited carriers. Here we demonstrate that Ag-Au alloys provide an ideal model system for controlling the optical and electrical responses in nanoscale thin metal films for hot carrier photodetectors with improved performance. While pure Ag and Au have long hot carrier attenuation lengths >20 nm, their optical absorption is insufficient for high efficiency devices. Instead, we find that alloying Ag and Au enhances the absorption by -50% while maintaining attenuation lengths >15 nm, currently limited by grain boundary scattering, although the electron attenuation length of pure Au outperforms pure Ag as well as all of the alloys investigated here. Further, our density functional theory analysis shows that the addition of small amounts of Au to the Ag lattice significantly enhances the hot hole generation rate. Combined, these findings suggest a route to high efficiency hot carrier devices based on metallic alloying with potential applications ranging from photodetectors and sensors to improved catalytic materials.
Keywords: electron attenuation length; hot carriers; metal alloys; near-infrared absorption; photodetection; Schottky photodiodes